Transcription Factors in Eosinophil Development and As Therapeutic Targets - Fulkerson, Patricia C. (Frontiers in Medicine, 2017)
Dynamic gene expression is a major regulatory mechanism that directs hematopoietic cell fate and differentiation, including eosinophil-lineage commitment and eosinophil differentiation. Though GATA-1 is well established as a critical transcription factor for eosinophil development, delineating the transcriptional networks that regulate eosinophil development at homeostasis and in inflammatory states is not complete. Yet, recent advances in molecular experimental tools using purified eosinophil developmental stages have led to identifying new regulators of gene expression during eosinophil development. Herein, recent studies that have provided new insight into the mechanisms of gene regulation during eosinophil-lineage commitment and eosinophil differentiation are reviewed. A model is described wherein distinct classes of transcription factors work together via collaborative and hierarchical interactions to direct eosinophil development. In addition, the therapeutic potential for targeting transcription factors to regulate eosinophil production is discussed. Understanding how specific signals direct distinct patterns of gene expression required for the specialized functions of eosinophils will likely lead to new targets for therapeutic intervention.